Characterization of hop-and-sink daphniid locomotion. (25th February 2019) - Skipper, A N; Murphy, D W; Webster, D R
Abstract: This study characterizes the hop-and-sink locomotion of Daphnia magna, a zooplankton species widely studied in a variety of biological fields. Time-resolved tomographic particle image velocimetry (tomo-PIV) is used to obtain 3D kinematics and flow field data with high spatial and temporal resolution. The kinematics data show that the daphniid's velocity quickly increases during the power stroke, reaching maximum accelerations of 1000 body lengths/s 2, then decelerates during the recovery stroke to a steady sinking speed. The hop-and-sink locomotion produces a viscous vortex ring located under each second antennae. These flow structures develop during the power stroke, strengthen during the recovery stroke, and then decay slowly during the sinking phase. The time records of vortex circulation are self-similar when properly normalized. The flow fields were successfully modeled using an impulsive stresslet, showing good agreement between the decay of circulation and a conceptual model of the impulse. While no relationships were found between kinematics or flow field parameters and body size, the total energy dissipated by the daphniid hop-and-sink motion was found to scale exponentially with the vortex strength.